International Cross-Listing of Chinese Firms - Liu, Li Xian (IGI Global, 2014)
International Cross-Listing of Chinese Firms examines the successful techniques and strategies that Chinese companies are using within their financial practices. It highlights the foreign-based multinational enterprise theories related to the major international stock markets. By providing the latest theories and research, this book will be beneficial for business practitioners, researchers, and managers interested in the relationship between cross-listing and firm valuation of Chinese firms.